Extraction, Structural Characterisation, and Immunomodulatory Properties of Edible Amanita hemibapha subspecies javanica (Corner and Bas) Mucilage Polysaccharide as a Potential of Functional Food - Utoomporn Surayot; Sutee Wangtueai; SangGuan You; Subramanian Palanisamy; Warawut Krusong; Charles S. Brennan; Francisco J. Barba; Yuthana Phimolsiripol; Phisit Seesuriyachan (Journal of Fungi, 2021)
This research aimed to extract mucilage polysaccharides (MP) from Amanita hemibapha subspecies javanica (Corner and Bas), and further fractionate them using anion-exchange chromatography, yielding two fractions (MPF1 and MPF2). The crude extract, and fractions mainly consisted of carbohydrates (83.5–93.2%) with minor amounts of proteins (5.40–7.20%), and sulphates (1.40–9.30%). Determination of the monosaccharide composition revealed that glucose was the major unit, followed by galactose, mannose, rhamnose, and arabinose. The average molecular weight (MW) of the crude extract and fractions was in the range 104.0–479.4 × 103 g/mol. Interestingly, the crude extract, and fractions did not cause any toxic effect in RAW264.7 cells. However, they stimulated the RAW264.7 cells to release nitric oxide and cytokines through the activation of nuclear factor-kappa B (NF-κB), and mitogen-activated protein kinase (MAPK) pathways via cell surface TLR4. Structural analysis of the most immunestimulating extract fraction, MPF2, revealed that the main backbone consisted of α-D-(1→6)-glucopyranoside. These results suggest that the MPs derived from A. hemibapha subspecies javanica (Corner and Bas) are potent in enhancing immunity; hence, they can be used as a functional ingredient in food products.